Teachers’ Opinion about Pharmacology Written Question Papers of MBBS Professional Examinations (Bangladesh Journal of Medical Education, 2021)
Written examination is an important method for juddering the learning of medical students. Short Answer Questions (SAQ) and multiple choice questions (MCQ) are introduced in MBBS curriculum to assess student cognitive domain. This cross sectional descriptive study was conducted to get the teachers’ opinion about Pharmacology professional written short answer question papers of different Universities of Bangladesh. For this purpose, opinion of total 56 purposively selected teachers of the Department of Pharmacology & Therapeutics of 20 Medical Colleges were collected through self-administered semi-structured questionnaire.  Most of the teachers (66% & 61%) were in favour of existing distribution of different types of question in curriculum (recall-60%, understanding -30% and problem based-10%) for short answer question paper (SAQ). Majority of the teachers (66% & 54%) were satisfied with the present coverage of recall and understanding type questions respectively but only 41% teachers were satisfied with the coverage of problem based type questions. Seventy-seven percent teachers were satisfied with content coverage in SAQ papers. Eighty-seven percent teachers were satisfied with present marking scheme on SAQ paper. Findings of this study may be used to redefine the distribution of different types question in SAQ papers and to improve the quality of question papers by ensuring their coverage.Bangladesh Journal of Medical Education Vol.12(1) 2021: 40-49